Antiaging Properties of Exosomes from Adipose-Derived Mesenchymal Stem Cells in Photoaged Rat Skin. (21st December 2020) - Liang, Jun-Xian; Liao, Xuan; Li, Sheng-Hong; Jiang, Xiao; Li, Ze-Hua; Wu, Yin-Di; Xiao, Li-Ling; Xie, Guang-Hui; Song, Jian-Xing; Liu, Hong-Wei
Abstract : Adipose-derived stem cells (ADSCs) have been documented as possible candidates for skin rejuvenation. However, the effects of ADSC-derived exosomes on photoaged skin remain to be fully elucidated. This study was aimed at determining the antiaging effects of ADSC-derived exosomes on photoaged skin. Human ADSCs were isolated from the adipose tissue of healthy women and cultured in vitro. Then, exosomes were extracted from the cultured ADSCs, purified by ultracentrifugation, and verified by examination of cell morphology using transmission electron microscopy and the identification of specific biomarkers. Meanwhile, the optimal exosome concentration and treatment time were selected. The photoaged skin model was created by subjecting Sprague-Dawley rats to ultraviolet B radiation. Exosomes were injected into the photoaged skin in a single therapeutic dose. The thickness of the epidermis and dermis was observed by HE staining. The relative mRNA expression of type I collagen, type III collagen, and matrix metalloproteinases (MMP-1 and MMP-3) was determined by real-time PCR. In the rat model of photoaged skin, the injected exosomes markedly decreased the epidermal thickness and increased the dermal thickness of the photoaged skin 7 days after treatment. Moreover, the proportion of the stratum corneum of the epidermis was decreased. Furthermore, real-time RT-PCR showed that the mRNA expression of type I collagen was increased and that of type III collagen, MMP-1, and MMP-3 was decreased. Our results demonstrate that ADSC-derived exosome treatment could significantly improve skin photodamage and that ADSC-derived exosomes may be a potential agent for photoaged skin treatment.